Association Analysis of BMD‐associated SNPs with Knee Osteoarthritis. (June 2014) - Yerges‐Armstrong, Laura M; Yau, Michelle S; Liu, Youfang; Krishnan, Subha; Renner, Jordan B; Eaton, Charles B; Kwoh, C Kent; Nevitt, Michael C; Duggan, David J; Mitchell, Braxton D; Jordan, Joanne M; Hochberg, Marc C; et al.
ABSTRACT Osteoarthritis (OA) risk is widely recognized to be heritable but few loci have been identified. Observational studies have identified higher systemic bone mineral density (BMD) to be associated with an increased risk of radiographic knee osteoarthritis. With this in mind, we sought to evaluate whether well‐established genetic loci for variance in BMD are associated with risk for radiographic OA in the Osteoarthritis Initiative (OAI) and the Johnston County Osteoarthritis (JoCo) Project. Cases had at least one knee with definite radiographic OA, defined as the presence of definite osteophytes with or without joint space narrowing (Kellgren‐Lawrence [KL] grade ≥ 2) and controls were absent for definite radiographic OA in both knees (KL grade ≤ 1 bilaterally). There were 2014 and 658 Caucasian cases, respectively, in the OAI and JoCo Studies, and 953 and 823 controls. Single nucleotide polymorphisms (SNPs) were identified for association analysis from the literature. Genotyping was carried out on Illumina 2.5M and 1M arrays in Genetic Components of Knee OA (GeCKO) and JoCo, respectively and imputation was done. Association analyses were carried out separately in each cohort with adjustments for age, body mass index (BMI), and sex, and then parameter estimates were combined across the two cohorts by meta‐analysis. We identified four SNPs significantly associated with prevalent radiographic knee OA. The strongest signal (p = 0.0009; OR = 1.22; 95% CI, 1.08–1.37) maps to 12q3, which contains a gene coding for SP7. Additional loci map to 7p14.1 (TXNDC3), 11q13.2 (LRP5), and 11p14.1 (LIN7C). For all four loci the allele associated with higher BMD was associated with higher odds of OA. A BMD risk allele score was not significantly associated with OA risk. This meta‐analysis demonstrates that several genomewide association studies (GWAS)‐identified BMD SNPs are nominally associated with prevalent radiographic knee OA and further supports the hypothesis that BMD, or its determinants, may be a risk factor contributing to OA development. © 2014 American Society for Bone and Mineral Research.